Efektivitas Pengawasan Penyiaran TV KABEL Berlangganan Oleh KPID Riau - ZULKARNAEN, DEDDY; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: Indonesian Broadcasting Commission (KPI) is an independent stateinstitution established by Act No. 32 of 2002 on broadcasting with the aim ofregulating everything about broadcasting in Indonesia. This independent bodymade up of KPI KPID center and its work in the area are coordinated, nationalpolicy defined KPIs and provincial level while the implementation into KPIDcoverage. The purpose of this study is to To determine the effectiveness of theimplementation of subscription cable TV broadcasting monitoring by KPID Riauand to determine the factors that influence the effectiveness of monitoring theimplementation of the broadcasting cable TV subscription by KPID Riau.Data analysis method used in this research is descriptive qualitativeanalysis method that is based on trying to explain the phenomena that exist andexplore all the facts relating to the subject matter covered by the research, namelythe effectiveness of supervision by subscribing to cable TV broadcasting KPIDRiau.Based on the research and the analysis that has been conducted on thisstudy, obtained by directly monitoring the effectiveness of the implemented KPIDRiau to subscribe to cable TV broadcasters, with a direct way to monitor the fieldby looking at their operating permit. And establishing a program organizationformed Community program Intelligent Media (KCM) and receive complaintsdirectly by phone, sms or in online.Pengawasan KPID Riau administration tosubscribe to cable TV broadcasting are based on the government regulation No..52 of 2005 on organizing and monitoring broadcasters subscribing to the field aswell as receiving information from the public about the existence of cable TVsubscription broadcasters are not taking care of the administrative permission.